Effect of exercise training on cardiac mitochondrial respiration, biogenesis, dynamics, and mitophagy in ischemic heart disease - Viloria, Mary Audrey D.; Li, Qing; Lu, Wang; Nhu, Nguyen Thanh; Liu, Yijie; Cui, Zhen-Yang; Cheng, Yu-Jung; Lee, Shin-Da (Frontiers in Cardiovascular Medicine, 2022)
Objective. Because cardiac mitochondrial dysfunction was found in Ischemic Heart Disease (IHD), this study determined the effects of exercise training (ET) on cardiac mitochondrial respiration and cardiac mitochondrial quality control in IHD. Methods. A narrative synthesis was conducted after searching English-written animal studies about ET’s effect on the cardiac mitochondrial function in IHD in three databases (PubMed, Web of Science, and EMBASE) until December 2020. Studies that used aerobic exercise as an intervention for at least three (3) weeks and had at least normal, negative (sedentary IHD), and positive (exercise-trained IHD) groups were included. Quality evaluation of included studies was done using the CAMARADES checklist. Results. The ten included studies (CAMARADES score: 6-7/10) used swimming or treadmill exercise for 3-8 weeks. Seven studies showed that ET ameliorated cardiac mitochondrial respiratory function as manifested by increased complexes I-V activity, SOD2, RCR, ND1, ND6, CytB, and ATP production, and attenuated ROS. Ten studies showed that ET improved cardiac mitochondrial quality control, as manifested by enhanced and/or controlled cardiac mitochondrial biogenesis, dynamics, and mitophagy. Four studies showed improved cardiac mitochondrial physiological characteristics. Conclusion. ET have caused improved cardiac mitochondrial function in IHD. Hence, this suggest that ET is a suitable medium for cardioprotection. Prospero Registration ID: CRD42021226817